2009
DOI: 10.1007/s10103-008-0636-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser irradiation and epidermal growth factor on adult human adipose-derived stem cells

Abstract: The study investigated the effects of low-level laser radiation and epidermal growth factor (EGF) on adult adipose-derived stem cells (ADSCs) isolated from human adipose tissue. Isolated cells were cultured to semi-confluence, and the monolayers of ADSCs were exposed to low-level laser at 5 J/cm(2) using 636 nm diode laser. Cell viability and proliferation were monitored using adenosine triphosphate (ATP) luminescence and optical density at 0 h, 24 h and 48 h after irradiation. Application of low-level laser i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 29 publications
6
58
1
4
Order By: Relevance
“…В некоторых работах [24][25][26] положительные результаты воздействия НИЛИ с длиной волны 635 нм достигаются при значительно большей ЭП 5 -Дж/см 2 , но касаются они стимулирования высво-бождения клетками эпидермального фактора роста (EGF). Возможно, различные физиологические проявления клеточной активности имеют место при вариациях энергетических и спектральных характе-ристик лазерного света.…”
Section: таблица 2 параметры нили-освечивания (лазерные излучающие гunclassified
“…В некоторых работах [24][25][26] положительные результаты воздействия НИЛИ с длиной волны 635 нм достигаются при значительно большей ЭП 5 -Дж/см 2 , но касаются они стимулирования высво-бождения клетками эпидермального фактора роста (EGF). Возможно, различные физиологические проявления клеточной активности имеют место при вариациях энергетических и спектральных характе-ристик лазерного света.…”
Section: таблица 2 параметры нили-освечивания (лазерные излучающие гunclassified
“…They have also been differentiated into smooth muscle cells that are functional [27]. These cells have also shown increased viability and proliferation when exposed to LILI alone [5] and, as well as, in combination with epidermal growth factor (EGF) [28]. Recent studies have demonstrated the functional neural differentiation of human ADSCs [29].…”
Section: Adipose Derived Stem Cellsmentioning
confidence: 99%
“…In addition, LILI has been shown to illicit different responses in different cell types depending on the intensity of irradiation. Molecular and cellular processes are inhibited or stimulated at different intensities of LILI as indicated by changes in metabolism, increased adenosine triphosphate (ATP) production and increased cellular migration [14]. Furthermore, LILI has also been shown to promote the proliferation of rat mesenchymal bone marrow, cardiac and ADSCs in vitro [14,15].…”
Section: Low Intensity Laser Irradiation (Lili)mentioning
confidence: 99%
“…Molecular and cellular processes are inhibited or stimulated at different intensities of LILI as indicated by changes in metabolism, increased adenosine triphosphate (ATP) production and increased cellular migration [14]. Furthermore, LILI has also been shown to promote the proliferation of rat mesenchymal bone marrow, cardiac and ADSCs in vitro [14,15]. It was recently demonstrated that not only do ADSCs respond well to external stimuli, including LILI, as a mechanism of inducing increased viability and proliferation, but differentiation into other cell lineages can be achieved with minimal invasive techniques such as careful selection and addition of growth factor combinations.…”
Section: Low Intensity Laser Irradiation (Lili)mentioning
confidence: 99%